Optimization of the anti-cancer activity of the phosphatidylinositol-3 kinase pathway inhibitor PITENIN-1: switching thiourea with 1,2,3-triazole - Kommagalla, Yadagiri; Cornea, Sinziana; Riehle, Robert; Torchilin, Vladimir; Degterev, Alexei; Ramana, Chepuri V. (Medchemcomm, 2014)
We previously reported encouraging in vitro and in vivo anti-cancer activity of N-((3-chloro-2-hydroxy-5-nitrophenyl)carbamothioyl) benzamide (termed PITENIN-1). In the current work, we describe the structure-activity relationship study of the PIT-1 series, based on the replacement of a central thiourea unit with 1,2,3-triazole, which leads to increased liver microsomal stability, drug likeness and toxicity towards cancer cells.